A modified high-fat diet and its effect on histopathological features of mice liver as an alternative diet for animal model of liver cell damage - Dzul Fithria Mumtazah; Hendri Busman; Mohammad Kanedi; Gina Dania Pratami (Biogenesis: Jurnal Ilmiah Biologi, 2021)
Researchers attempted to obtain animal models that experienced hypercholesterolemia and led to liver damage to determine the performance of the liver. Rats were chosen because of the ease of handling, collecting organ and blood samples. Still, their high price and availability that are more difficult to find have made some researchers look for alternatives to other animal models such as mice. This study aims to determine the role of a modified high-fat diet as an alternative diet for mice to experience hepar damage. Male mice treated for four and eight weeks with a modified high-fat diet were sacrificed for their liver, then they were tested for histopathology using the paraffin method and HE staining. The characterization of hepar damage traits was carried out to score the degree of parenchymal degeneration, hydropic degeneration, and necrosis. The results showed that the control group, four and eight weeks of atherogenic diet had more than 50% cell damage, presumably due to the role of the starch mixture in feed as a source of carbohydrates through the mechanism of converting carbohydrate pathways into fat which damages liver cells.